Expressive Arts and Mindfulness: Aiding Adolescents in Understanding and Managing Their Stress. Issue 3 (3rd July 2018) - Lindsey, Laura; Robertson, Phyllis; Lindsey, Beth
ABSTRACT: This study contains an exploration of the use of mask-making and mindfulness training as components of an expressive arts group intervention designed to help youth understand and manage their stress. With the assistance of a school counselor, six eighth-grade students, who were having difficulty managing stress, were identified and participated in a 12-hour group intervention over the course of six weeks. Participants were assessed pre- and post-intervention and at a three-week follow-up on measures of self-efficacy, depression, anxiety, and stress. The group intervention resulted in significant self-reported reductions of anxiety and stress at the three-week follow-up.